Innate Lymphoid Cells: Expression of PD-1 and Other Checkpoints in Normal and Pathological Conditions - Mariotti, Francesca Romana; Quatrini, Linda; Munari, Enrico; Vacca, Paola; Moretta, Lorenzo (Frontiers in Immunology, 2019)
Innate lymphoid cells (ILCs) belong to a family of immune cells. Recently, ILCs have been classified into five different groups that mirror the function of adaptive T cell subsets counterparts. In particular, NK cells mirror CD8+ cytotoxic T cells while ILC1, ILC2 ILC3, and Lymphoid tissue inducer (LTi)-like cells reflect the function of CD4+T helper (Th) cells (Th1, Th2 and Th17 respectively). ILCs are involved in innate host defenses against pathogens and tumors, in lymphoid organogenesis, and in tissue remodeling/repair. In recent years, important molecular inducible checkpoints (PD-1, TIM3, and TIGIT) were shown to control/inactivate different immune cell types. The expression of many of these receptors has been detected on NK cells and subsets of tissue-resident ILCs in both physiological and pathological conditions, including cancer. In particular, it has been demonstrated that the interaction between PD-1+ immune cells and PD-L1/PD-L2+ tumor cells may compromise the anti-tumor effector function leading to tumor immune escape. However, while the effector function of NK cells in tumor is well established, limited information exists on the other ILC subsets. We will summarize what is known to date on the expression and function of these checkpoint receptors on NK cells and ILCs, with a particular focus on the recent data that reveal an essential contribution of the blockade of PD-1 and TIGIT on NK cells to the immunotherapy of cancer. A better information regarding the presence and the function of different ILCs and of the inhibitory checkpoints in pathological conditions may offer important clues for the development of new immune therapeutic strategies.